Long-Term Results of Stenting of Left Main Coronary Artery Lesions: Experience of One Hospital - Olena V. Levchyshyna; Sergii V. Salo; Yevhenii V. Aksonov (Український журнал серцево-судинної хірургії)
The aim. To study the effectiveness of left main coronary artery (LMCA) stenting in patients with coronary heart disease and to optimize the choice of percutaneous coronary intervention technique based on the experience of one clinic.